A review of the tensile and fatigue responses of cellulosic fibre-reinforced polymer composites - Dhar Malingam, Sivakumar; Ng, Lin Feng; Jenal, Ruztamreen; Mustafa, Zaleha; Subramonian, Sivarao (Taylor and Francis Inc., 2020)
The use of polymer-based composites has been gaining popularity in the industry over the last few decades. Their high strength to weight ratio and high fatigue resistance make these composites the preferred materials for a wide variety of applications. The current trend has inclined towards hybrid fibre reinforced composites owing to their outstanding characteristics compared to non-hybrid composites. Numerous research works have been conducted to study the fatigue life behaviour of such composite materials. This study addressed the monotonic and dynamic performance of non-hybrid and hybrid natural fibre based composite materials, and the factors that influence their fatigue performance, along with the stiffness decay of each composite material. Most studies have shown the superior potential of using natural fibres in place of synthetic fibres in those critical applications that involve tensile and cyclic loading.